The Correlation between Social Media Use and Cyber Victimization: A Research on Generation Z in Turkey - Murat Erdoğdu; Murat Koçyiğit (Connectist Istanbul University Journal of Communication Sciences)
Although social media usage has many advantages, it also brings many risks. Anger, hate and bullying actions by individuals are frequently encountered on social media platforms today. Thus, this study aims to determine whether there is a meaningful correlation between social media use and cyber victimization. The cyber victimization levels of the users were investigated using the data of research conducted online with 390 participants (Generation Z) and social media users. The purposeful sampling method was used to select the participants. In the analysis of the data, frequency analysis, pearson correlation analysis and linear regression analysis were performed using the statistical package program. It was found that the frequency of exposure of users to cyberbullying behaviors is low. It was determined that there are significant correlations at p=.01 and p=.05 levels between the independent variables of the sub-dimensions (socializing, obtaining information, sharing, following, and making use of leisure time) of the social media usage scale and the dependent variables of the cyber victimization sub-dimensions (cyber harassment, fraud, sharing and exclusion of private information, and virtual struggle and anxiety).